Are Dietary Patterns of Mothers during Pregnancy Related to Childrens Weight Status? Evidence from the Lifeways Cross-Generational Cohort Study - Celine M Murrin; Mirjam M Heinen; Cecily C Kelleher (AIMS Press, 2015)
Children's diet patterns are likely to be influenced by their mothers' diet pattern. The primary objective of this study was to examine whether children's adiposity could be influenced by diet patterns of mothers during pregnancy. A secondary objective was to study the relative influence of fathers' and children's dietary patterns on childhood adiposity. The design was a prospective cross-generational cohort study initiated with 1,124 mothers recruited during pregnancy. Self-reported questionnaires included a food frequency instrument (FFQ) to assess parental intakes during the perinatal period. Child body mass index (BMI) was measured at 5 years and an age-appropriate FFQ was administered. Dietary patterns for each group were identified by principal components analysis. Pearson's correlation and logistic regression were used to test for associations. Dietary patterns were described for n = 1,042 mothers during pregnancy and n = 331 fathers during the perinatal period. Dietary patterns and BMI data were available for n = 443 children at age 5 years. The diet patterns identified for mothers correlated with the corresponding diet patterns for fathers. The children's "pasta & vegetable" pattern was positively correlated with "healthy patterns" in mothers (r = 0.195, p < 0.01) and fathers (r = 0.250, p < 0.01). The children's "junk" food pattern was correlated with the "processed" pattern in mothers (r = 0.245, p < 0.01) and fathers (r = 0.257, p < 0.01). In multivariate logistic regression analysis the upper tertiles of children's "cereal and juice" [Tertile 2 (T2): OR 0.44, 95% CI (0.22-0.90); T3: 0.41, (0.19-0.85)] and the middle tertile of the "pasta and veg" patterns [T3: 0.37, (0.18-0.75)] were negatively associated with overweight and obesity. The mothers' processed pattern during pregnancy was positively associated with offspring overweight and obesity [T2: 2.64, (1.28-5.45); T3: 2.03, (0.87-4.73)]. No significant associations were observed for the paternal diet patterns. This analysis shows that the influence of maternal diet pattern on child obesity is apparent early in the lifecourse.